Cinnamaldehyde Exerts Its Antifungal Activity by Disrupting the Cell Wall Integrity of Geotrichum citri-aurantii - OuYang, Qiuli; Duan, Xiaofang; Li, Lu; Tao, Nengguo (Frontiers in Microbiology, 2019)
Our previous study showed that cinnamaldehyde (CA) significantly inhibited the mycelial growth of Geotrichum citri-aurantii, one of the main postharvest pathogens in citrus fruits. This study investigated the antifungal mechanism of CA against G. citri-aurantii. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images showed that CA treatment led to clear morphological changes in the cell walls and membranes of G. citri-aurantii. However, the membrane integrity, total lipids and ergosterol contents were not apparently affected by CA treatment. Notably, the extracellular alkaline phosphatase (AKP) activity was increased after CA treatment, suggesting impairment in cell wall permeability. A weakened fluorescence in the cell wall, a decrease in the chitin contents, and changes of ten genes involved in cell wall integrity were also observed. These results suggested that CA may exhibit its antifungal activity against G. citri-aurantii by interfering the build of cell wall and therefore lead to the damage of cell wall permeability and integrity.